2009
DOI: 10.1089/fpd.2009.0290
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Siderophore Receptor and Porin Proteins-Based Vaccine to Control the Burden ofEscherichia coliO157:H7 in Feedlot Cattle

Abstract: The E. coli O157:H7 SRP-based vaccine might serve as a preharvest intervention to reduce the burden of E. coli O157:H7 on cattle presented for harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…H7 flagellin has also been demonstrated to act as an adhesion factor, and anti-H7 antibodies reduce the level of binding of bacteria to primary cell cultures (27). Despite high antibody titers following vaccination with these antigens, vaccination is only partially protective (13,14,(28)(29)(30)(31), while antibody titers are inconsistently correlated with bacterial shedding (32)(33)(34). The serological response of cattle to colonization has also been studied extensively, and antibodies against O157 lipopolysaccharide (LPS), H7, Tir, intimin, EspA, EspB, EspD, EspM2, NleA, TccP, Stx1, and Stx2 have been demonstrated (25,(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…H7 flagellin has also been demonstrated to act as an adhesion factor, and anti-H7 antibodies reduce the level of binding of bacteria to primary cell cultures (27). Despite high antibody titers following vaccination with these antigens, vaccination is only partially protective (13,14,(28)(29)(30)(31), while antibody titers are inconsistently correlated with bacterial shedding (32)(33)(34). The serological response of cattle to colonization has also been studied extensively, and antibodies against O157 lipopolysaccharide (LPS), H7, Tir, intimin, EspA, EspB, EspD, EspM2, NleA, TccP, Stx1, and Stx2 have been demonstrated (25,(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…An important approach to protect human health from EHEC infections is the development of vaccines that limit or prevent shedding from cattle. Despite the progress in this area, we have a limited understanding of the natural or vaccine-based protection that has been demonstrated in a number of studies [15,17,20,23,31]. EHEC O157 colonization of cattle has been modelled in one other paper [32] using a stochastic birth -death process of bacterial growth in different compartments of an animal's gut.…”
Section: Discussionmentioning
confidence: 99%
“…These include a type III secretion system that injects a cocktail of up to 40 different effector proteins into the host cell, driving intimate attachment and manipulating innate responses to promote the persistence of the organism in the animal's gastrointestinal tract [9][10][11][12][13]. A number of approaches to limit shedding of the organism from cattle have been tested, including vaccines that aim to generate responses against these colonization factors [14][15][16][17][18]. Cattle colonized at the terminal rectum can shed up to 10 7 EHEC O157 per gram of faeces, leading to the term 'supershedders' [18].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the capture of iron is blocked, inducing a disadvantageous competitive state of O157:H7 compared to other bacteria that normally colonize the bovine intestine. 171 Several research trials conducted to quantify the efficacy of SRP protein-based vaccines in feedlot cattle, demonstrate that the prevalence of E. coli O157 was lower, with a significant reduction of E. coli O157 concentration in fecal samples (98.2%). Furthermore, the number of days that cattle were culture positive for E. coli O157 and that they were identified as high shedders, was reduced.…”
Section: Enterohemorragic Escherichia Colimentioning
confidence: 99%
“…Finally, the results showed that the timing of vaccination in calves and the dose regimen of the SRP vaccine reduced the prevalence of E. coli O157: H7. [171][172][173][174] Three systematic reviews [124][125][126] have analyzed the available literature on trials performed in domestic ruminants infected naturally or artificially, and have concluded that both Econiche Ò and Epitopix Ò significantly decrease the colonization and stool load of O157:H7. However, these vaccines do not eliminate O157:H7 completely, and it is not known if they generate cross-protection against other STEC serogroups that represent a highest risk of severe illness and even death in young children and the elderly (O26, O103, O45, O111, O121 and O145; named "top 6").…”
Section: Enterohemorragic Escherichia Colimentioning
confidence: 99%